2020
DOI: 10.2215/cjn.12581019
|View full text |Cite
|
Sign up to set email alerts
|

A Primer on Congenital Anomalies of the Kidneys and Urinary Tracts (CAKUT)

Abstract: Congenital anomalies of the kidneys and urinary tracts (CAKUT) are disorders caused by defects in the development of the kidneys and their outflow tracts. The formation of the kidneys begins at week 3 and nephrogenesis continues until week 36, therefore, the kidneys and outflow tracts are susceptible to environmental risk factors that perturb development throughout gestation. Many genes have been implicated in kidney and outflow tract development, and mutations have been identified in patients with CAKUT. In s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(117 citation statements)
references
References 61 publications
2
79
0
12
Order By: Relevance
“…In addition to reduced nephron, impaired nephrogenesis can cause a wide spectrum of defects in the kidney and urinary tract, namely congenital anomalies of the kidney and urinary tract (CAKUT) [ 35 ]. Unlike adults, CAKUT is one of the major causes of CKD in children [ 36 ].…”
Section: Developmental Origins Of Cvd and Kidney Disease: Human Evidencementioning
confidence: 99%
“…In addition to reduced nephron, impaired nephrogenesis can cause a wide spectrum of defects in the kidney and urinary tract, namely congenital anomalies of the kidney and urinary tract (CAKUT) [ 35 ]. Unlike adults, CAKUT is one of the major causes of CKD in children [ 36 ].…”
Section: Developmental Origins Of Cvd and Kidney Disease: Human Evidencementioning
confidence: 99%
“…The major developmental events include UB formation, UB branching morphogenesis, formation of bladder and kidney, kidney tubule branching, and nephrogenesis [ 49 ]. Impaired branching morphogenesis and nephrogenesis can cause low nephron endowment and a spectrum of defects in the kidney and urinary tract, namely congenital anomalies of the kidney and urinary tract (CAKUT) [ 50 ]. The developing kidneys are vulnerable to environmental risk factors that impair development throughout gestation: a malformed kidney is a severe defect happening during early pregnancy, whereas defects that occur later are generally less severe [ 50 ].…”
Section: Developmental Origins Of Kidney Diseasementioning
confidence: 99%
“…The corollary to this strategy is a prediction that unless severe, most subjects with low nephron number will not develop ESRD until after peak reproductive years, when selection pressure is low. 109 Consistent with this prediction, a Norwegian study of over 2 million subjects revealed that low birth weight, IUGR, and preterm birth represent cumulative risk factors for development of ESRD that is delayed until later adulthood. 110 The aging kidney.…”
Section: Metabolic Control Of Nephron Numbermentioning
confidence: 84%
“…108 Congenital anomalies of the kidneys and urinary tracts can result from genomic, epigenomic, or environmental stressors in any combination, and the more severe the nephron deficit, the sooner the onset of CKD and the more rapid its progression. 109 Human life history strategy favors allocation of energy to the developing brain through physiologic adaptation by the fetal cerebral circulation, 53 and by metabolic regulation of organ development by nuclear and mitochondrial gene transcription regulated epigenetically (Fig. 4).…”
Section: Metabolic Control Of Nephron Numbermentioning
confidence: 99%